Pengaruh Terapi Mindfulness Walking terhadap Kecemasan pada Mahasiswa: Quasi Eksperimen - Rasendria Wahyu Isnanto; Erydani Anggawijayanto (LPPM Institut Pendidikan Nusantara Global, 2026)
Anxiety in young adult/university students remains elevated and affects academic functioning and well-being. This study evaluated the effectiveness of Mindfulness Walking in reduction anxiety and compared outcomes across two delivery settings (rural vs urban). The hypothesis proposed that anxiety decreases after the intervention and differs between settings. Participants were 17 university students aged 18-25 years in Yogyakarta (rural n=9; urban n=8). Data were collected using the Beck Anxiety Inventory before and after six sessions of Minfulness Walking (30 minutes per session). Analyses comprised assumption checks (Shapiro-Wilk; Levene) and a significant post-intervention difference between groups (F=4.843; p=0.045); adjusted means were lower in the urban group (21.3) than in the rural group (31.5), with Cohen’s d=1.07 indicating a large practical effect. These findings indicate that Mindfulness Walking effectively reduces anxiety in students, with stronger effectiveness observed in the urban setting.